Modifications of major pigment content of Chlorella vulgaris cultured in different media - Nguyen, Thi Dong Phuong (Hue University Journal of Science: Natural Science, 2025)
Currently, to avoid the harmful effects of artificial dyes, scientists strongly encourage the use of natural pigments derived from organisms such as microalgae. Although microalgae are known to outperform all other microorganisms in terms of pigment production, their natural occurrence is insufficient for the increasing commercial demand. Therefore, further enhancing the pigment production in the algae cells is of tremendous significance. Some environmental factors known to regulate natural pigment synthesis are changes in pH, temperature, light, salinity and nutrients of the environment. This study indicates that further manipulation of major nutrient parameters, such as nitrogen (N), phosphorus (P), and carbon (C), in the culture medium can be the easiest way to intervene among other physical parameters with the aim of cultivating microalgae at an industrial scale and commercial production. It also emphasises that if the N content is doubled compared with the standard Bold’s Basal Medium (BBM), the Chlorophyll a content obtained will be higher, reaching (37 ± 0.08) mg/L, while doubling the P content cannot increase chlorophyll production but increases carotenoid synthesis with the highest content compared with the remaining media. Similarly, replacing the C source of glucose with NaHCO3 also changes the synthesis of pigments, and the concentrations of chlorophyll a, b and carotenoids are all higher than in BBM. Therefore, the results of this study might indicate that if the N/P ratio is doubled compared with its ratio in the BBM medium, the ability to synthesise chlorophyll and carotenoids will increase. This will be the basis for cultivating microalgae in other environments besides the traditional BBM medium to collect chlorophyll or pigments.